Factors Affecting Balance Performance in Adolescents - Milena Kovačević; Rastislava Krasnik; Aleksandra Mikov; Darko Mikić; Jelena Zvekić-Svorcan; Dragana Vukliš; Dajana Dedić Novaković; Marina Đelić (MDPI AG, 2024)
(1) Background: The influence of different factors on balance in adolescence is assessed by conducting functional balance tests that examine its different components. (2) Materials and methods: The study sample comprised 110 healthy adolescents of both sexes, aged 12-18 years. Single Leg Stance with Eyes Open (SLS-EO) and Eyes Closed (SLS-EC) tests were conducted to evaluate static balance, whereas the Functional Reach Test (FRT) and Lateral Reach Test (LRT) were performed to establish functional stability limits. The influence of sex, age, demographic factors, anthropometric characteristics, participation in sports activities, and trunk extensor muscle endurance (Biering-Sorensen test) on balance performance was determined through correlational and univariate linear regression analyses. (3) Results: Older age (Beta [β] = 0.247; 95% CI [0.75, 5.20]; p < 0.01) and better trunk extensor muscle endurance (β = 0.224; 95% CI [0.015, 0.13]; p < 0.05) were significant predictors of the SLS-EO results, while younger age (β = −0.219; 95% CI [−1.32, −0.11]; p < 0.05) and higher muscle percentage (β = 0.237; 95% CI [0.06, 0.48]; p < 0.05) emerged as significant predictors of LRT performance, and greater bone mass was a significant predictor of FRT results (β = 0.444; 95% CI [3.62, 8.17]; p < 0.01). However, none of the independent variables was a statistically significant predictor of the SLS-EC results. (4) Conclusions: The current study found that age, trunk extensor muscle endurance, muscle percentage, and bone mass are significant predictors of different balance components, suggesting that balance is task-specific.